Experimental analysis of polymer matrix composite microstructures under transverse compression loading. (May 2022) - Flores, Mark; Sharits, Andrew; Wheeler, Robert; Sesar, Nathan; Mollenhauer, David
Abstract: Strengthening the fundamental understanding of micromechanical methods in continuity is a critical aspect in developing and designing future composite systems. Virtual testing has provided additional understanding of the behavior of materials on a microstructural scale. However, experiments must be executed to determine their validity. Modeling realistic microstructures under realistic loading conditions could help develop physically based micromechanical constitutive laws needed to predict their intrinsic failure. In this study, a micropillar with varying sizes was manufactured out of continuous fiber reinforced composites and transversely compressed to observe micromechanical phenomena. The fiber shape, size, and distribution were recorded as well as stress vs strain curves for each size of micropillar. The specimens were speckled to perform 2D digital image correlation (DIC) to analyze displacement and strain contours of the surface. The results from this study provides basic knowledge of microstructural instabilities, effects of nanovoids, interfacial debonded and matrix crack formation while under transverse compressive loading.